Management of Spasticity in Cerebral Palsy: An Electroencephalogram-Oriented Novel Approach - Jaseja, Harinder (Journal of Pediatric Neurology, 2020)
Cerebral palsy (CP) is commonly associated with spasticity though the exact pathophysiology is still unknown. Management of spasticity is an important aspect of care because it can adversely affect quality of life. Patients with CP also commonly exhibit interictal epileptiform discharges (IEDs) on their electroencephalograms (EEGs) even without clinical epilepsy. This brief article studies the relationship between spasticity and IEDs. Based on the intrinsic relationship between the two and available pathophysiological evidence of spasticity, the author suggests a mandatory EEG in all patients with CP and spasticity and consideration for initiation of IEDs when detected.
Keywords: interictal epileptiform discharges in CP with spasticity; pathophysiology of spasticity; electroencephalogram in CP with spasticity